The Influence of the Modeling the Way Strategy on Fiqh Learning of Prayer Material to Improve Deep Learning-Based Learning Outcomes at Mambaul Ulum Middle School - Arifin, Syamsul; Wahab, Wahab (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the effect of the Modelling The Way strategy on Fiqh learning of prayer material on improving Deep Learning-based learning outcomes at Madrasah Tsanawiyah Mambaul Ulum. The approach used is mixed methods, which is a combination of qualitative and quantitative approaches. Qualitatively, the study describes the learning process carried out by Fiqh teachers through exemplary behavior (uswah hasanah), while quantitatively, student learning outcomes are measured through multiple-choice tests, essays, prayer practice rubrics, and affective questionnaires. The research subjects consisted of 20 eighth-grade students at MTs Mambaul Ulum in the 2025/2026 academic year. Data were collected through observation, learning outcome tests, worship practice assessments, and Likert scale questionnaires. The results showed that the application of the Modelling The Way strategy had a significant effect on improving student learning outcomes in all domains. The average cognitive score was 8.00 (80%), comprehension score was 15.00 (75%), psychomotor score was 24.00 (96%), and affective score was 95%. Qualitative results show that teachers as role models succeeded in fostering students' spiritual awareness, discipline, and devotion in performing prayers. Deep Learning-based learning strengthened students' ability to understand spiritual meaning and internalize the values of worship into their daily lives. Thus, the Deep Learning-based Modelling The Way strategy proved to be effective in improving Fiqh learning outcomes, both cognitively, affectively, and psychomotorically, as well as being able to shape the religious and spiritual character of students in madrasahs.